The political economy of public sector governance - Bertelli, Anthony Michael (Cambridge University Press, 2012)
"In The Political Economy of Public Sector Governance, Anthony Michael Bertelli introduces core ideas in positive political theory as they apply to public management and policy. Though recent literature that mathematically models relationships between politicians and public managers provides insight into contemporary public administration, the technical way these works present information limits their appeal. This book helps readers understand public-sector governance arrangements and the implications these arrangements have for public management practice and policy outcomes by presenting information in a non-technical way"--